Vaccination strategies in multiple sclerosis patients with Delphi methodology: A Turkish consensus - Cinar, Bilge Piri; Tuncer, Asli; Cetinkaya, Levent; Akbas, Oguz; Agalar, Canan; Aluclu, Mehmet Ufuk; Siva, Aksel (Asean Neurological Assoc, 2025)
Background: Both the presence of multiple sclerosis (MS) and the use of immunomodulatory therapy for this disease can change the vaccine response in individuals with MS. In this study, due to the lack of guidelines for vaccination of MS patients in our country, the aim was to create a Delphi consensus on vaccination practices and vaccine types in MS patients. Methods: The Real-time Delphi technique, a more structured and predefined version of the traditional Delphi study was used to ensure a comprehensive research process. The stages of the structured online Delphi application process, which includes repeated rounds, (three rounds) are applied. Fifteen participants are sufficient to achieve homogeneous outcomes according to expertise criteria and in this study, the group comprised 31 experts who met these criteria and participated in all stages. Results: The assessment of the level of consensus among panelists revealed that there was almost perfect consensus on 16 items and significant consensus on 12 items. When examining the items in which the panelists did not reach a consensus, it was found that there was minor consensus (slight-1) on 1 item, and there was no consensus (indicate poor-0) on 2 items. Conclusion: We wanted to share a country practice and our current recommendations on vaccination strategies, by making use of articles containing country-based recommendations and working-group recommendations, as well as our national experiences.
Keywords: multiple sclerosis; Delphi technique; vaccination; practical approach